Bioenergetic Assessment and Economic Efficiency of Predecessors and Fertilizer Systems in the Cultivation of Winter Wheat - Nikolaevich Neshchadim, Nikolay; Alekseevich Kvashin, Aleksandr; Nikolaevna Gorpinchenko, Ksenia; Petrovich Fedulov, Yuriy; Alekseevich Salfetnikov, Anatoliy (International Journal of Engineering and Technology, 2018)
The influence of a type of crop rotation, the predecessor and various doses of mineral fertilizers on the yield of winter wheat was examined. The studies were conducted at the North Kuban Agricultural Experimental Station in two 10-field rotations – grain tillage and grain-grass tillage – in the course of a prolonged stationary experiment. The soil was ordinary chernozem, low in humus, deep, with the humus content in the arable (0-30 cm) soil layer equaling to 3.95-4.00% depending on the nutrient status, the content of mineral nitrogen equaling to 5.9-8.3 mg/kg of soil, and the content of exchangeable potassium equaling to 330-360 mg/kg of soil.It has been established that from the point of view of bioenergetic and economic efficiency, the most favorable predecessors for cultivation of winter wheat should be considered sainfoin and winter wheat, and for the rotation of sainfoin – peas. Maize harvested for grain and sugar beet are more time-consuming and energy-consuming tillage predecessors. Among the applied fertilizer systems, the best economic and bioenergetic indicators were obtained by using medium and higher doses of complete mineral fertilizer.